2020
DOI: 10.1055/s-0040-1701253
|View full text |Cite
|
Sign up to set email alerts
|

To Share is Human! Advancing Evidence into Practice through a National Repository of Interoperable Clinical Decision Support

Abstract: Background Healthcare systems devote substantial resources to the development of clinical decision support (CDS) largely independently. The process of translating evidence-based practice into useful and effective CDS may be more efficient and less duplicative if healthcare systems shared knowledge about the translation, including workflow considerations, key assumptions made during the translation process, and technical details. Objective Describe how a national repository of CDS can serve as a publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Advancing Evidence into Practice through a National Repository of Interoperable Clinical Decision Support," describes how the use of the Agency for Healthcare Research & Quality's CDS-Connect can provide a platform for peer-to-peer sharing of CDS tools. 10 The United States is among the global leaders in the implementation of electronic health records (EHRs) and HIT 11,12 ; however, the U.S. health care system lags behind comparable countries in most health care measures despite spending comparatively more per person. For example, in 2018, while the U.S. spent $10,586 on health care per capita (more than twice of Canada), 13 its life expectancy was 78.54 years, lower than Canada's 82.47 years.…”
mentioning
confidence: 99%
“…Advancing Evidence into Practice through a National Repository of Interoperable Clinical Decision Support," describes how the use of the Agency for Healthcare Research & Quality's CDS-Connect can provide a platform for peer-to-peer sharing of CDS tools. 10 The United States is among the global leaders in the implementation of electronic health records (EHRs) and HIT 11,12 ; however, the U.S. health care system lags behind comparable countries in most health care measures despite spending comparatively more per person. For example, in 2018, while the U.S. spent $10,586 on health care per capita (more than twice of Canada), 13 its life expectancy was 78.54 years, lower than Canada's 82.47 years.…”
mentioning
confidence: 99%
“…This Collaborative emphasises development of digital infrastructure to support the Knowledge Ecosystem, a cycle of Action-Data-Evidence-Guidance that mirrors the LHS cycle. It has further been active in developing groups such as COKA, the COVID-19 Knowledge Accelerator Initiative 14 [74], a response focused on COVID-19 to the call by Dunn and Bourgeois [73] to aim for computable knowledge synthesis and representation, through the use of standards such as EBMonFHIR 15 [79] and CPGonFHIR 16 , or rule formalisms for computational clinical guideline specification [80].…”
Section: Discussionmentioning
confidence: 99%
“…Translation of new knowledge into practice (Q3) required evidence synthesis approaches such as systematic reviews, critically involving searching (information retrieval), screening, appraisal, and meta-analysis of research publications. Key conclusions were rapidly shared via actively maintained, living guidelines [ 15 ] and platforms [ 16 ] or tools [ 17 ] for making available clinical decision support knowledge artifacts.…”
Section: A Global Learning Covid-19 Systemmentioning
confidence: 99%
“…27 These algorithms could also be implemented in EHR-agnostic authoring tools, such as CDS Connect. 28 It is intriguing that all sites had demonstrable errors, yet none were aware of them. In our previous work on CDS anomalies, we learned that clinicians may not be aware of such errors 6 and showed that many types of build and conceptualization errors were common.…”
Section: Discussionmentioning
confidence: 99%